Midlatitude Ionospheric Dynamics and Disturbances. - Kintner, Paul M. (Geophysical monograph, 2013)
Published by the American Geophysical Union as part of the Geophysical Monograph Series. Filling the need for a 20-year lag in substantial consideration of the midlatitude ionosphere, this volume focuses on work that takes advantage of GPS and UV imaging from satellites over the past decade, two methods that have profoundly transformed our understanding of this stratum of the atmosphere. Its interdisciplinary content brings together researchers of the solar wind, magnetosphere, ionosphere, thermosphere, polar and equatorial ionospheres, and space weather. Modeling and assimilat.